(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This paper presents a mathematical model of a solar battery designed for analyzing energy processes in autonomous power supply systems. The model is based on the current-voltage (I–V) characteristic of a photovoltaic converter and takes into account the influence of key internal and external factors, including illumination, temperature, and the angle of incidence of solar radiation. Using computer simulation methods, the characteristics of a single solar cell as well as solar batteries formed by series, parallel, and series-parallel connections are investigated. The obtained simulation results confirm the adequacy of the developed model and its applicability for evaluating energy balance and designing power supply systems.